Vitaminas B1, B6, B12 e Complexo B na prevenção da discinesia orofacial induzida por haloperidol em ratos : avaliação comportamental e mecanismos associados - Oliveira, Gersilene Valente de (2015)
Tardive dyskinesia (TD) is characterized by involuntary movements, mostly at lower face, near the mouth, with convulsion that can be light or hard. Is one severe disorder related, but restricted the antipsychotic therapy. Antipsychotic treatments above all the class of typical, like haloperidol (HAL) increase the risk of TD. The pathophysiology of TD is associated to a instability in neurotransmission system, such as dopaminergic and cholinergic, among others, as well as with oxidative instability mainly in brain areas related to the control of movement, as the striatum. B vitamins, in turn, show antioxidants effect and are cofactors to enzymes related to the synthesis of neurotransmitters. In this context, the present study aimed to determine the preventive effects of B1, B6, B12 vitamins or B complex against orofacial dyskinesia (OD) induced by HAL in rats. To do this male Wistar rats were intraperitoneally administered HAL (1 mg/kg, i.p.) for 21 days or concomitantly received HAL, B1 (60 mg/kg), B6 (60 mg/kg) or B12 (0,6 mg/kg) vitamin subcutaneously alone or in association. B complex consisted in the mix of 3 vitamins in equal proportions. One group of animals was administered with clozapine (25 mg/kg), an atypical antipsychotic not related to the development of OD. Behavioral tests were performed at the 1st, 7th and 21st days of drugs administration. The behavioral tests performed were locomotor activity, catalepsy and chewing vacuous movements. At 21st day the animals were sacrificed and had their brain areas dissected for neurochemical analysis. The results showed that HAL increased catalepsy time at 7th day and OD at 21st day. Administration of B vitamins (B1:B6:B12) alone or in association, together with HAL, prevented the development of OD and in a lower extension, catalepsy. Preventive effect of B vitamins was accompanied by restoration of the levels of reduced glutathione (GSH) and lipid peroxidation. Beyond the antioxidant effects, B vitamins increased the activity of the enzyme acetylcholinesterase (AChE) in all brain areas studied, with the maximum increase of activity observed in the hippocampus of animals co-administered with B12 vitamins and B vitamins cocktail. Clozapine did not induce OD and increase in the activity of AChE. Analysis of the expression of receptors and enzymes related to the synthesis of neurotransmitters in striatum by PCR-RT revealed that HAL increased the expression of the dopaminergic receptors D1 and D2 and reduce an expression of the muscarinic receptors M1. Haloperidol decreased the expression of tyrosine hydroxylase (TH), a limiting step for the synthesis of dopamine. Taken together the results suggest that B vitamins prevented changes induced by HAL, presenting thus a promising role as a preventive approach against HAL-induced OD.